IMPACT OF NEURAL NETWORKS ON WEBSITE DEVELOPMENT AND PROSPECTS FOR REPLACING FRONT-END DEVELOPERS - Brazhnikov, V.; Hashutina, Ye.; Bredikhin, V.; Bredikhin, D. (Municipal economy of cities (Technical science), 2024)
In the dynamic field of web development, neural networks have become pivotal, offering revolutionary approaches to website creation. As technology advances, these networks transition from being mere tools to catalysts for innovation, addressing the growing need for personalization, optimization, and functionality in web resources. However, with the increasing capabilities of neural networks, questions arise about their potential to replace traditional web developers. This article examines the role of neural networks in modern web development, analysing the prospects and challenges of their potential to supplant human developers. Recent research highlights the collaborative potential between humans and AI in web development, significantly enhancing efficiency, quality, and speed. Notable works include the automation of design aspects using neural networks, automatic code generation, and user behaviour analysis to optimize user experience (UX). Collaboration between humans and artificial intelligence (AI) is a promising direction in website development. This collaboration can significantly increase the efficiency, quality and speed of creating web resources. Tools like generative adversarial networks (GANs), neural networks for UI optimization, and AI-driven website builders like Stunning.so, Durable, and Framer AI exemplify these advancements. These tools can automate routine tasks, rapidly generate website designs, and optimize content for various devices, allowing developers to focus on more creative aspects. The article aims to explore the impact of neural networks on the web development process, identifying potential benefits and challenges. While neural networks can automate and optimize many aspects of web development, enhancing productivity and quality, they also pose risks such as loss of creativity, security concerns, dependence on technology, and potential job displacement. Balancing these factors is crucial for leveraging the full potential of neural networks in web development, ensuring they complement rather than completely replace traditional methods.